Pengaruh Infrastruktur Pelabuhann Terhadap Arus Barang (Throughput) Pada Pelabuhan Soekarno Hatta Makassar - Asmiati Asmiati; Sulastriani Sulastriani (Journal of Innovative and Creativity, 2025)
This study aims to analyze the influence of port infrastructure on the flow of goods (throughput) at Soekarno Hatta Port, Makassar. The research approach used a quantitative method with a survey of 102 respondents directly involved in port operational activities. Data were analyzed using linear regression to determine the extent to which infrastructure contributes to increased throughput. The results show that port infrastructure has a significant effect on the flow of goods. Improvements in the quality of physical facilities, the capacity of loading and unloading equipment, and the smooth operation of operational support systems have been proven to increase the port's ability to handle cargo volume. These findings emphasize the importance of infrastructure development as a key strategy in improving port performance and strengthening supply chain efficiency in eastern Indonesia.